THE IMPORTANCE OF LEGAL EDUCATION AND ADVOCACY IN INCREASING LEGAL LITERACY AMONG THE YOUNG GENERATION IN UZBEKISTAN - Saydirasulov Asadbek Akmalovich; Saydirasulova Muxlisa Akmalovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Legal literacy among youth is essential for fostering responsible citizenship and active civic participation. In Uzbekistan, legal education and advocacy help young people understand their rights, apply laws in daily life, and engage with societal issues. This article examines the role of schools, universities, and advocacy programs in promoting legal awareness, identifies key challenges, and suggests strategies to strengthen youth legal literacy. Enhancing legal knowledge among the younger generation is vital for building a just and stable society.